SUBSTITUSI TEPUNG AMPAS TAHU TERHADAP KUALITAS COOKIES - Marizalni, Izza; Yusuf, Liswarti; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2013)
This study aimedtoanalyze the effect ofsubstitution inthe composition oftofupowderas much as0%, 25%, 35% and45% of thequality ofcolor, neatnessshape, uniformity ofshape, fragrantpulp,luster, brittletexture, fine texture, sweetness, flavorpulpknowandsavorycookies. Thisis thekind of researchexperimentusinga completely randomized design/perfectwiththenumberonefactorflourtofuwithcomposition(0%, 25%, 35%, 45%) as much asfourtimes thereplications/trialconductedinworkshopCateringDepartmentfamilywelfarePadang State Universityengineering facultyin April2013.Panelistsare studentswho have graduatedCateringcoursesPastryandFood Processingwhichnumbered 30people. Data analysisis avariantanalysisandDuncantest. Hypothesis test resultsshow thatthere isan influence on theuse oftofuflour25%, 35% and45% on the quality ofcookies. Tofuflourcompositionsuggeststhattheuse oftofupowderas much as35% givea better effecton the quality ofthe fragrance, shapeuniformity, qualitysavoryflavor, sweetness, frailtyandquality offlavorthat is nottoodominanttofu. Whilethecomposition oftofupowderas much as25% did nothave a significant influenceonall indicators. Onthe composition oftofupowderas much as45% had a significant influenceon allindicators.